TIKTOK SHOP: CONSUMER CULTURE TRANSFORMATION IN THE ERA OF SOCIAL MEDIA - Prasetyorini, Ema; Suprajang, Sandi Eka (DIVERSITY Logic Journal Multidisciplinary, 2023)
Background. The presence of social media has transformed human communication and interaction patterns. Communication typically occurred through face-to-face interactions. However, in the modern era, thanks to technological advancements, communication can take place without the need for physical meetings. Research Purpose. This research aims to analyze changes in consumer culture in the context of TikTok Shop, a social media-based video platform connecting users to virtual stores, particularly among millennial female students in the Blitar Raya area. Research Method. This study employs a qualitative descriptive method. Data collection is carried out through unstructured interviews using purposive sampling. This research was conducted on students in the Blitar Raya area using sample selection criteria. The data analysis in this research is conducted using scaling measurement. Findings. Consumption patterns on the TikTok Shop social media platform include the intensity of watching live streaming and short videos containing product reviews from buyers. Millennial students in Blitar tend to consider online shopping as an effective and efficient method. They trust the authenticity of products more because promotions on the TikTok Shop social media platform create the impression that they can see the products as if in a physical store. Conclusion. Through this research, it is hoped that society can become more aware of the influence of social media on consumer behavior, avoiding falling into false consciousness and resisting the allure of advertising. Furthermore, the role of capitalism in fostering consumer behavior by blurring the line between wants and needs should also be given attention.